Rizal without the overcoat - Ocampo, Ambeth R. 1961- (Anvil Publishing, Inc., 2022)
"This book is a collection of essays from Ambeth R. Ocampo’s newspaper column “Looking Back” that began in the Philippine Daily Globe and later moved to the Philippine Daily Inquirer. He presents a readable and painless introduction to Jose Rizal and offers fascinating insights, lively anecdotes, academic intrigue, and little-known facts about the hero as human. Investigating Rizal’s own writings - his diaries, letters, and other papers – Ocampo attempts to strip the countless myths and rumors that surround the national hero."